A new era? : Timor-Leste after the UN - Ingram, Sue; Kent, Lia; McWilliam, Andrew (State, society and governance in Melanesia (Series), 2015)
"Timor-Leste has made rapid progress in its first decade as a new state, casting aside the instability that blighted its early years and achieving strong economic growth and institutional development. During 2012, the nation experienced peaceful presidential and parliamentary elections, the winding-up of the Australia-led International Stabilisation Force, and the completion of the United Nations (UN) peacekeeping mission after 13 years of UN presence. But significant challenges remain for the fledgling nation as it struggles to diversify its economy, implement its ambitious social and economic development plans, and preserve stability in the face of projected declines in petroleum revenues. To mark this transition and reflect on the road ahead for Timor-Leste, the College of Asia and the Pacific at The Australian National University (ANU) convened an inaugural Timor-Leste Update on 28-29 November 2013. ... The Timor-Leste Update was designed with a number of complementary objectives in mind. Firstly, it was intended to contribute to Australia's developing knowledge of and engagement with a close regional neighbour by providing a public forum to discuss recent developments and plans. The Update also aimed to sustain and strengthen relationships between government agencies, civil society organisations and research institutions working on Timor-Leste, while helping to build the profile and capacity of East Timorese researchers and policy analysts."--Introduction.